เครื่องมือประเมินความสุขของผู้สูงอายุ - พลอยชมพู มณีสุขเกษม (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The research is Measurement Study research. The objective is to build the questionnaire and pilot measuring a happiness of elderly. Data were collected from 78 elderly people. Questionnaires included: 1) General background 2) Happiness Assessment Tool for Elderly People 3) WHOQOL – BREF –THAI.Happiness Assessment Tool for Elderly People was developed as a multi-dimensional self-rating questionnaire to measure happiness and to guide keys to improve happiness of individual elderly.Reliability of Happiness Assessment Tool for Elderly People is high (0.887), correlation with WHOQOL-BREF-THAI (r) is0.738 (p value<0.01); content validity has a good and significant and factor loading of 7 components from factor analysis are 0.615 - 0.840; It has good construct validity from factor analysis, which showed 7 components. This tool is appropriate for quantify happiness of Thai elderly in residential home.